(untitled) (Journal of Applied Oral Science, 2022)
Miller's class I gingival recessions (GR) have been treated using coronally advanced flap (CAF) with platelet-rich fibrin membrane (PRF membrane) or connective tissue graft (CTG). Objective: The aim of this study was to evaluate the effect of different multiple layers of PRF membranes for the treatment of GR compared with the CTG procedure. Material and Methods: Sixty-three Miller class I GR were treated in this study. Twenty-one GR selected randomly were treated with two layers of PRF membranes+CAF in 2PRF+CAF (test group-1), four layers of PRF membranes+CAF in 4PRF+CAF (test group-2), and CTG+CAF in the control group. The plaque index (PI), gingival index (GI), probing depth (PD), keratinized tissue thickness (KTT), clinical attachment level (CAL), recession depth (RD), recession width (RW), and keratinized tissue height (KTH) measurements were performed at baseline and 1, 3, and 6 months after surgery. The post-operative discomfort of patients, assessed with the visual analog scale (VAS) and healing index (HI), was recorded after surgery. Results: PI, GI, and PD scores were similar for all patients at all times. RD and RW scores were similar for each patient at 1 month, but these values were significantly increased in the subsequent periods in test group-1. The increase in KTT was significantly higher in the control group compared with the test groups. Similar root coverage scores were obtained in the test group-2 and control groups, and these scores were significantly higher compared with test group-1. Conclusions:The PRF membrane+CAF technique may be an alternative to the CTG+CAF technique for postoperative patient comfort. However, PRF membranes should use as many layers as possible.